Analisis Makna Dalam Lirik Single-Single Lagu Karya Soegi Bornean - Amalia, Ineu Tuting; Agustiani, Tanti (Jurnal Bahastra, 2024)
Semiotics is the study of signs (sign). According to Ferdinand De Saussure's semiotic theory, the most important subject of Saussure's theory is the principle that language is a system of signs, and each sign is composed of two parts, namely the signifier and the signified. This study focuses on analyzing the meaning contained in the song lyrics of Soegi Bornean's singles entitled "Semenjana", "Samsara", and "Pijaraya" using descriptive qualitative methods with the aim of describing the meaning contained in the lyrics of the singles. songs by Soegi Bornean entitled "Semenjana", "Samsara", and "Pijaraya". Based on the results of the research, the lyrics of Soegi Bornean's singles entitled Semenjana", "Samsara", and "Pijaraya" contain a very deep meaning of life. The song entitled “Semenjana” teaches us that in life we must instill a simple attitude. In the song "Samsara" there is a message that we must include sincerity in our lives, because sincerity is a symbol of maturity. Whereas the single song entitled "Pijaraya" teaches us to instill goodness and always make calm as a foothold, then happiness will come. In researching the song lyrics of Soegi Bornean's singles, Ferdinand de Saussure's semiotic analysis is used. Saussure's theoretical model focuses more on direct attention to the sign itself.